Obesity, smoking status and their relationships in selected population groups - Petra Lenártová; Martina Gažarová; Jana Mrázová; Jana Kopčeková; Marta Habánová; Peter Chlebo; Kristina Jančichová (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Overweight and obesity are defined as abnormal or excessive fat accumulation that may impair health. Obesity is associated with many chronic diseases, including cardiovascular disease and diabetes, and recently the role of overweight and obesity in lung disease has received new interest. Chronic obstructive lung disease is the third-leading cause of death globally, and both obesity and diet appear to play roles in its pathophysiology. Cross-sectional studies have demonstrated an inverse association between obesity and the prevalence of chronic obstructive pulmonary disease (COPD). Objective. This study aims to evaluate the relationship between smoking, lipid profile and obesity (body composition changes) in a selected groups of population (30 non-smokers, 30 smokers and 60 COPD patients). Material and Methods. We evaluated fat mass, fat free mass, body mass index and lipid profile in a group of 120 randomly selected probands (60 COPD patients; 30 smokers without COPD; 30 non-smokers without COPD) to identify possible negative relationships of smoking to body composition. To the measurement of fat mass (FM) and fat free mass (FFM) was used a device Bodystat Quadscan 4000 (Bodystat Ltd, British Isles). The device works by using four-frequency bioelectrical impedance analysis. Laboratory parameters as total cholesterol (T-C), high-density cholesterol (HDL-C), low-density cholesterol (LDL-C) and triacylglycerols (TG) were investigated by automated clinical chemistry analyzer LISA 200th. The measured values were statistically processed and evaluated in a statistical program STATISTICA Cz. Version 7.1. (Kruskall-Wallis test). Results. A comparison of the mean fat mass we found statistically highly significant differences between the group of COPD patients and non-smokers (P <0.001) and insignificant differences (P ≥ 0.05) between the other groups of our experiment. A comparison of the mean fat mass values of all three groups of the experiment shows a steady increase in fat from non-smokers (17.66 ± 10.04 kg) to COPD patients with the highest mean value (25.08 ± 10.14 kg). In the group of COPD patients we recorded the lowest average value of FFM (51.76 ± 13.84 kg), in group of smokers the middle (56.06 ± 10.76 kg) and in non-smokers the highest average value of FFM (59.91 ± 9.90 kg) at relatively the same body weight in the groups. Based on calculated body mass index (BMI), we found in group of COPD patients overweight in 15 cases (25%), obesity in 7 patients (11.67%), severe obesity in 14 patients (23.3%) and morbid obesity in 2 patients (3.33%); in the group of smokers overweight in 16 cases (53.33%), obesity in 5 cases (16.6%) and severe obesity in 1 case (3.33%); in non-smokers we recording overweight in 14 cases (46.67%), obesity in 5 cases (16.67%) and severe obesity in 2 cases (6.67%). In the lipid profile of the monitored groups of probands, we observed statistically significant differences only for LDL cholesterol (LDL-C). There was a statistically significant difference (P <0.001) between the group with COPD and smokers, as well as between the group of smokers and non-smokers (P < 0.05). Conclusions. In the vast majority of patients with COPD, the lung damage that leads to COPD is caused by long-term cigarette smoking. The presence and absence of risk factors such as smoking, inappropriate lipid profile and obesity (amount of fat mass) in selected population groups were observed. Additional studies to explore both the quantitative and qualitative changes in body composition with disease process of COPD are required.